Pemanfaatan Framework Laravel Dalam Pembangunan Sistem Penjualan Alat Instrumentasi Listrik - Ade Maman Suherman; Esron Rikardo Nainggolan (Department of Information Technology, Universitas Timor, Indonesia, 2021)
Marketing a product is usually done by offering to the most meet people, distributing brochures and other traditional methods. However, if the product being offered is not a consumer product for everyone, the way to market it must be different. In today's technology, we can use digital media to market products, such as a sales website. By using the waterfall methodology and assisted by a framework such as Laravel, we can make a website more neat, organized and structured. With the hope that the website can increase the percentage of sales in order to achieve the company's targets.